ANALYSIS OF COMPOSITE ACTION OF PRECAST HOLLOW CORE SLABS AND CAST IN PLACE MESH REINFORCED CONCRETE TOPPING - Omer, Sajjad (2019)
Considering composite action of hollow core slab with cast in place mesh reinforced concrete topping helps to provide longer hollow core slabs and reduces the overall weight of the structure. Research has shown that composite action normally can be attained through studs or other connecting elements from the bottom element but for hollow core slabs the roughness of the top surface is enough to attain the composite action. This study aims to analyze the composite action of hollow core slabs made of ELEMATIC sections with thicknesses 150mm and 265mm with cast in place mesh reinforced topping. The thickness of topping was considered as 65mm for 150mm thick hollow core slab and 70mm for 265mm thick hollow core slabs. A load test setup was made for both 150mm thick hollow core slab and 265mm thick hollow core slab which mirrored the actual site condition. The connecting reinforcements were provided as per normal practice and the supports were considered as simply supported after which the topping was setup with the wire mesh and the concrete poured. Readings from the three gauges below the hollow core slabs were recorded at 0% loading, 25% loading, 50% loading, 75% loading, 100% loading, 100% sustained loading and 0% released load condition after 24 hours. For 150mm thick hollow core slabs, 0.29mm was the deflection for 100% sustained loading and for 265mm thick hollow core slabs, 3.36mm was the deflection for 100% sustained loading. These two values are way less than the actual estimated values. The results indicate that composite actions are valid for uncracked hollow core slab sections considered in the tests. Further investigations can confirm the composite action for other hollow core slab sections and also for section which are cracked